2004
DOI: 10.1016/j.jhsb.2004.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic Contracture in an Infant’s Forearm – A Case Report

Abstract: We present a case of a gradually developing ischaemic contracture of the forearm muscles of an infant who developed without any trauma or acute gangrene at birth. Release of the middle and ring finger digitorum profundus muscles and pronator quadratus at 2 years of age corrected the deformity. Histopathology showed no evidence of fibromatosis or any other tumor. Although a dynamic splint was used to maintain the range of motion, the range of the middle finger motion deteriorated gradually 2 years after surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(21 reference statements)
1
2
1
Order By: Relevance
“…In this case, as with most documented cases,116 sequelae are atrophy, scarring, mobility limitation and probable limitation of bone growth. The study by Ragland et al showed skeletal involvement in 18 cases and nerve lesions in 16 out of 24, with neurological recovery in four 9…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In this case, as with most documented cases,116 sequelae are atrophy, scarring, mobility limitation and probable limitation of bone growth. The study by Ragland et al showed skeletal involvement in 18 cases and nerve lesions in 16 out of 24, with neurological recovery in four 9…”
Section: Discussionsupporting
confidence: 68%
“…The histological characteristics are unspecified and the necrosis severity is related to ischemia duration 4. In the cases previously described, there is no evidence of compression in other anatomical regions 116. However, in the present case a few discreet skin lesions were detected in other regions that may be related to slight compression from conflict of intrauterine compartment.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…3 Fewer than 100 cases have been reported in the literature. 4 In almost all reported cases, NCS is not associated with any type of fracture or dislocation. The exact etiology remains unknown, but the insult occurs before birth.…”
Section: Discussionmentioning
confidence: 97%